A new framework for developing and evaluating complex interventions: update of Medical Research Council guidance. (30th September 2021) - Skivington, Kathryn; Matthews, Lynsay; Simpson, Sharon Anne; Craig, Peter; Baird, Janis; Blazeby, Jane M; Boyd, Kathleen Anne; Craig, Neil; French, David P; McIntosh, Emma; Petticrew, Mark; Rycroft-Malone, Jo; et al.
Abstract : The UK Medical Research Council's widely used guidance for developing and evaluating complex interventions has been replaced by a new framework, commissioned jointly by the Medical Research Council and the National Institute for Health Research, which takes account of recent developments in theory and methods and the need to maximise the efficiency, use, and impact of research.